2018
DOI: 10.1016/j.jsat.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Access to treatment for alcohol use disorders following Oregon's health care reforms and Medicaid expansion

Abstract: The study examines impacts of delivery system reforms and Medicaid expansion on treatment for alcohol use disorders within the Oregon Health Plan (Medicaid). Diagnoses, services and pharmacy claims related to alcohol use disorders were extracted from Medicaid encounter data. Logistic regression and interrupted time series analyses assessed the percent with alcohol use disorder entering care and the percent receiving pharmacotherapy before (January 2010-June 2012) and after (January 2013-June 2015) the initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A handful of studies have examined receipt of medications for the treatment of alcohol or opioid use disorder using Medicaid or commercial claims data. A recent study using data from the Oregon Medicaid program found that the percentage of patients with an alcohol use disorder diagnosis receiving a medication increased from 2.3% in 2010 to 3.8% in 2015 [104]. Similar data from the Oregon Medicaid program showed that the percentage of enrollees with an opioid use disorder diagnosis who received a medication did not significantly change from 2010 to 2016.…”
Section: Medicaid and Commercial Claims Datamentioning
confidence: 95%
“…A handful of studies have examined receipt of medications for the treatment of alcohol or opioid use disorder using Medicaid or commercial claims data. A recent study using data from the Oregon Medicaid program found that the percentage of patients with an alcohol use disorder diagnosis receiving a medication increased from 2.3% in 2010 to 3.8% in 2015 [104]. Similar data from the Oregon Medicaid program showed that the percentage of enrollees with an opioid use disorder diagnosis who received a medication did not significantly change from 2010 to 2016.…”
Section: Medicaid and Commercial Claims Datamentioning
confidence: 95%
“…The finding that Medicaid insurance was associated with significantly decreased AUD treatment was concerning and may be due to several interrelated factors. Overall, Medicaid insurance expansion has led to increased access to AUD treatment [23,24]. However, Medicaid enrollees often have restricted access to providers and specialty services compared to those with private insurance [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations from the OPTIONS-DC, implemented in February 2018, resulted in significantly higher use of dalbavancin for treatment or completion of treatment at 27.4% compared to those with substance use disorder (SUD) who did not have an OPTIONS-DC (9%). 16 This highlights that successful coordination of dalbavancin courses begins prior to hospital discharge, and requires comprehensive planning, because patients may be unreachable once they leave.…”
Section: Discussionmentioning
confidence: 99%